Albanian language in public use - Dulaj, Fridrik (Technium Social Sciences Journal, 2022)
For many years linguistic studies have been seen started to see in different views. Technological changes, like information and telecommunication are affecting also Albanian language. Our purpose on this paper is to make visible those linguistic development that came from commercial enterprises. In order to be more competitive in Kosovo’s market or maybe to be closer with costumers they are using the same language as in advertisings ex. N’ETC krejt iki (you have got all in ETC), Nuk a shefiktu (the boss is not here), O babpo del uji mi tok(hej dad the water is over the ground) etc. Or like it is shown in commercial enterprises. Familjadhemiqt (friends and family).N’trip, Merrebubinhinn’trip( take the puppy in the trip) Ipkonejaoshtknej (the party is here), hej, zog mobile (bird mobile), folshlire (talk free), hej! Eshte cool! (is cool) 4.5 cent, mos e nal me krejt! ( for only 4.5 cent don’t stop with all), hej! Evente, hej! (Hej events) Apps. The source for this paper are ads on TV.